1996
DOI: 10.1073/pnas.93.10.5116
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is involved in heat-induced cell death in Saccharomyces cerevisiae.

Abstract: The cause for death after lethal heat shock is not well understood. A shift from low to intermediate temperature causes the induction of heat-shock proteins in most organisms. However, except for HSP104, a convincing involvement of heat-shock proteins in the development of stress resistance has not been established in Saccharomyces cerevisiae. This paper shows that oxidative stress and antioxidant enzymes play a major role in heat-induced cell death in yeast. Mutants deleted for the antioxidant genes catalase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
248
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(261 citation statements)
references
References 33 publications
(24 reference statements)
12
248
0
1
Order By: Relevance
“…Several previous authors have also reported involvement of SOD in temperature stress tolerance (Upadhyaya et al 1990;Jagtap and Bhargava 1995;Davidson et al 1996). Gupta and Gupta (2005) also reported that SOD activity in two wheat genotypes increased with increase in temperature although the magnitude was comparatively lower in the susceptible (Blokhina et al 2003;Babu and Devraj 2008).…”
Section: Discussionmentioning
confidence: 90%
“…Several previous authors have also reported involvement of SOD in temperature stress tolerance (Upadhyaya et al 1990;Jagtap and Bhargava 1995;Davidson et al 1996). Gupta and Gupta (2005) also reported that SOD activity in two wheat genotypes increased with increase in temperature although the magnitude was comparatively lower in the susceptible (Blokhina et al 2003;Babu and Devraj 2008).…”
Section: Discussionmentioning
confidence: 90%
“…In our experiments, the observation that PGK promoter stimulation was observed only at midlog phase in cells cultured in PQ-containing medium, and not after a 1 h exposure to the oxidant, further supports the notion that PGK is especially required in the recovery stage. Furthermore, it should be pointed out that both oxidative stress and heat shock are uncoupIers of mitochondrial respiration (19,20), and that heat shock may cause increased 0;-production (21). A recent report by Yoo et al (22) indicates that both PQ and heat shock activates the CU,ZnSOD gene (SODl) promoter through the same heat shock element (HSE).…”
Section: Discussionmentioning
confidence: 99%
“…2Ј,7Ј-Dichlorofluorescin diacetate is hydrolyzed by an esterase after incorporation into yeast cells, and its hydrolyzed product, 2Ј,7Ј-dichlorofluorescin, reacts with peroxides to give 2Ј,7Ј-dichlorofluorescein, a fluorescent label (36). Cells grown exponentially in SD minimal medium were collected and resuspended in fresh SD medium containing 0.01 mM 2Ј,7Ј-dichlorofluorescin diacetate.…”
Section: Methodsmentioning
confidence: 99%